Comparative analysis of the hunting laws between Republic of North Macedonia and several Southeast European countries, in terms of game and hunting grounds management - Cokoski, Kristijan; Maletic, Vladimir; Risteski, Mihajlo (My University, 2019)
ABSTRACT: In this study, we presented an analysis based on the management practices of the game and hunting grounds, comparing the hunting laws of the North Macedonia, Republic of Serbia, Republic of Croatia, Republic of Slovenia, and Republic of Bulgaria. We conducted a comparative and content analysis between North Macedonia`s hunting law, and the hunting laws implemented in the four other, above listed countries in the region. For this purpose, we analyzed the common legal acts between each of the hunting laws, and we determined the uncommon legal acts and different practices between each of the selected countries. We also determined the strengths and weaknesses in the legislation and practices aiming successful management of the game and hunting grounds. From the results of the analysis, we concluded: a) parallels in the law concepts, but still odds in the practically implemented hunting law, for each of the addressed countries, b) the legislation for hunting in the Republic of Serbia, Republic of Croatia, Republic of Slovenia, and Republic of Bulgaria, implements more common practices in comparison with the hunting law of North Macedonia, and c) the North Macedonia`s hunting law abounds with shortcomings, inconsistences and unenforceable provisions leading to major negative impacts in the practical managing with the game and hunting grounds.
Keywords: hunting, hunting law, hunting grounds, content analysis